Estabelecimento Da Rede Moçambicana dos Defensores de Direitos Humanos (RMDDH) Nas Províncias de Tete, Gaza, Nampula - RMDDH (CDD - Centro para Democracia e Desenvolvimento Mozambique, 2021)
A Rede Moçambicana dos Defensores de Direitos Humanos (RMDDH) está a levar a cabo actividades de identificação e mapeamento de defensores de direitos humanos nas províncias, que incluem pessoas singulares e organizações da sociedade civil que estão na linha de frente na luta pela defesa dos direitos humanos. Financiado pela OCISA, o trabalho iniciou em Abril último na Província de Tete, centro de Moçambique, onde a RMDDH realizou vários encontros com organizações da sociedade civil que trabalham na área dos direitos humanos e com instituições governamentais e estatais
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Gaza; GP - Nampula; GP - Tete; L - portuguese / português; civil society / sociedade civil

Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social